2018
DOI: 10.1111/plb.12843
|View full text |Cite
|
Sign up to set email alerts
|

Germination niche breadth varies inconsistently among three Asclepias congeners along a latitudinal gradient

Abstract: Species responses to climate change will be primarily driven by their environmental tolerance range, or niche breadth, with the expectation that broad niches will increase resilience. Niche breadth is expected to be larger in more heterogeneous environments and moderated by life history. Niche breadth also varies across life stages. Therefore, the life stage with the narrowest niche may serve as the best predictor of climatic vulnerability. To investigate the relationship between niche breadth, climate and lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 87 publications
(103 reference statements)
2
35
1
Order By: Relevance
“…A wet regime (an approximation for the wettest localities, i.e., rainfall 2700 mm) was simulated by watering the Petri dishes with demineralized water (water potential 0.0 MPa). A dry regime was simulated by decreasing the water potential by adding polyethylene glycol (PEG, molecular weight 6000) into the water, which is a commonly‐used method (see e.g., Shahriari et al, 2014; Finch et al, 2019). To simulate the driest localities, i.e., precipitation of 600 mm per year, we reduced the water potential to –0.7 MPa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wet regime (an approximation for the wettest localities, i.e., rainfall 2700 mm) was simulated by watering the Petri dishes with demineralized water (water potential 0.0 MPa). A dry regime was simulated by decreasing the water potential by adding polyethylene glycol (PEG, molecular weight 6000) into the water, which is a commonly‐used method (see e.g., Shahriari et al, 2014; Finch et al, 2019). To simulate the driest localities, i.e., precipitation of 600 mm per year, we reduced the water potential to –0.7 MPa.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, germination is highly responsive to the immediate environment of the seeds (e.g., Grime et al, 1981; Khan and Gulzar, 2003; Shahriari et al, 2014; Finch et al, 2019) as well as to the environment of their origin (e.g., Roach and Wulff, 1987; Cendán et al, 2013; Walter et al, 2016; Finch et al, 2019). Recent studies found considerable intraspecific variation in germination percentage, with populations from the warmest conditions showing the highest germination in all study treatments (Santo et al, 2015) or at least one study treatment (e.g., Ndihokubwayo et al, 2016; Bauk et al, 2017; Mira et al, 2017).…”
mentioning
confidence: 99%
“…A result that suggests an interaction between source climate and life history (Finch et al . ). Based on an analysis of the intraspecific plasticity exhibited in morphology, colour and chemical composition of seeds of four populations of Astragalus aquilanus , Di Cecco et al .…”
Section: Changing Environmental Effectsmentioning
confidence: 97%
“…Yearly variation in thermal niche breadths can be influenced by environmental conditions experienced by maternal plants. However, shifts towards broader thermal response breadths seem unlikely for L. arenicola given its very narrow distribution [19,23]. This is problematic as the average annual temperature in the region where L. arenicola grows is about 23.8 • C. This value is already above the optimum thermal range (i.e., 20-22 • C) for germination of non-dormant seeds and germination response appears sensitive to temperatures above this range.…”
Section: Multi-dimensional Germination Niche Breadthmentioning
confidence: 99%
“…Specialization tends to be favored by species occurring in temporally stable environments (e.g., warm, tropical climates), while temporally unstable environments (e.g., temperate climates) tend to promote a generalist strategy [18][19][20][21]. Additionally, niche breadths are known to vary among populations and within succeeding generations of a population [22,23]. Clarification of a species germination niche breadth has implications for other questions related to determination of species diversity in a given area, similarities between species and relationships to coexistence, partitioning of an environment between species, how species within a community shape inter-species evolution, and adaptation of individuals at the population level [18,20].…”
Section: Introductionmentioning
confidence: 99%